2015
DOI: 10.1158/1055-9965.epi-14-0963
|View full text |Cite
|
Sign up to set email alerts
|

How Do Differences in Treatment Impact Racial and Ethnic Disparities in Acute Myeloid Leukemia?

Abstract: Background: We previously demonstrated disparate acute myelogenous leukemia (AML) survival for black and Hispanic patients; these differences persisted despite younger ages and higher prevalence of favorable cytogenetics in these groups. This study determined: (i) whether there are differences in treatment delivered to minorities, and (ii) how these differences affect outcomes in AML. We hypothesize that differences in treatment explain some proportion of survival disparities.Methods: We used California Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 33 publications
4
54
3
1
Order By: Relevance
“…The third study used the California cancer registry to analyze the racial differences in the use of chemotherapy, did not adjust for potential confounders such as socioeconomic factors, and demonstrated a lower rate of use of chemotherapy in African Americans. 10 This study had suggested that future studies should explore the role of socioeconomic factors and treatment facility location on leukemia care disparity. The study from Denmark 13 highlighted that the utilization of intensive chemotherapy was lower among older patients, particularly those with lower education and lower income levels.…”
Section: Discussionmentioning
confidence: 97%
“…The third study used the California cancer registry to analyze the racial differences in the use of chemotherapy, did not adjust for potential confounders such as socioeconomic factors, and demonstrated a lower rate of use of chemotherapy in African Americans. 10 This study had suggested that future studies should explore the role of socioeconomic factors and treatment facility location on leukemia care disparity. The study from Denmark 13 highlighted that the utilization of intensive chemotherapy was lower among older patients, particularly those with lower education and lower income levels.…”
Section: Discussionmentioning
confidence: 97%
“…While black patients with any type of WHO AML-NOS had an increased risk of death when compared to white patients, black patients with AML-RGA had risk levels similar to that of white patients. It has been recognized for some time that black patients with AML generally have worse outcomes than do white patients [11, 29-32], but recent work by Patel et al [33] indicate that is most likely not due to a higher incidence of AML of a high-risk subtype. These authors also propose that the survival disadvantage of black patients arises primarily from lack of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that black patients have had less access to chemotherapy and/or HSCT. A recent study using CCR data linked to hospital discharge data showed that the odds of receipt of HSCT and chemotherapy were lower among black than non-black patients (Patel, et al 2015a). …”
Section: Discussionmentioning
confidence: 99%
“…All of the variables considered had a priori hypothesized or previously observed (Bradley, et al 2011, Patel, et al 2015a, Percival, et al 2015, Pulte, et al 2013, Walter, et al 2011, Wolfson, et al 2012) associations with early death or survival. We also hypothesized that sociodemographic factors would have a greater impact on survival in older versus younger patients and investigated this hypothesis by analysing the hazard of death by age group.…”
Section: Methodsmentioning
confidence: 99%